Training and Practice for Modern Day Archaeologists - Jameson, John H.; Eogan, James; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
In recent years, an important and encouraging development has been the markedly increased number of collaborations among archaeologists, educators, preservation planners, and government managers, creating interdisciplinary approaches, methods, and solutions to archaeological heritage management. But what is the collective experience of archaeologists and cultural heritage specialists in these arenas? Should we be encouraged, or discouraged, by national and international trends? In order to answer these questions, Training and Practice for Modern Day Archaeologists explores a relatively new development in archaeology and historical preservation: new approaches to archeological and heritage education and training that accommodate globalization and the realities of the 21st century worldwide. The volume examines how the government, universities, and private sector meet, albeit not always, the educational and practical needs of practicing archaeologists today. This volume gets to the heart of a number of relevant issues: the international mobility of archaeologists and heritage managers; the problems of sustaining employment in a volatile market; employment of archaeologists in managing the archaeological impact of development projects; training partnerships; and the generation and interpretation of archaeological data and knowledge that results from such projects. In the 21st century, it seems likely that an increasing proportion of archaeological survey, excavation, and conservation work will be undertaken to mitigate the impact of developments. To derive maximum benefits (academic, societal and professional) from this work, our archaeological practices need to evolve. The papers in this volume contribute to a greater understanding of the need for these new forms of practice. Thus, Training and Practice for Modern Day Archaeologists is an invaluable resource for archaeologists, heritage preservation specialists, resource managers, educators and trainers, site managers, and anybody interested in the conservation of world heritage.
Keywords: Social sciences; Humanities; Archaeology; Social Sciences; Archaeology; Cultural Heritage